2019
DOI: 10.1530/edm-19-0006
|View full text |Cite
|
Sign up to set email alerts
|

A thyroid gland with over 30 foci of papillary thyroid carcinoma with activating BRAF V600E mutation

Abstract: Summary Multifocal papillary thyroid carcinoma (PTC) is common and the number of tumor foci rarely exceeds ten. The mechanism of multifocal disease is debated, with the two main hypotheses consisting of either intrathyroidal metastatic spread from a single tumor or independent multicentric tumorigenesis from distinct progenitor cells. We report the case of a 46-year-old woman who underwent total thyroidectomy and left central neck lymph node dissection after fine-needle aspiration of bilateral thyroid nodules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In addition, with the improvement of diagnostic procedures, most of the tumor diameter is small when it is detected. Nevertheless, PTC confined to isthmus has been reported to be more aggressive than the nodule located at lobes (15)(16)(17). Young Chan Lee et al (18) considered that isthmic PTC was more likely to be accompanied by capsule invasion and the pretracheal or prelaryngeal lymph nodes metastasis, being consistent with the other studies reported (19,20).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In addition, with the improvement of diagnostic procedures, most of the tumor diameter is small when it is detected. Nevertheless, PTC confined to isthmus has been reported to be more aggressive than the nodule located at lobes (15)(16)(17). Young Chan Lee et al (18) considered that isthmic PTC was more likely to be accompanied by capsule invasion and the pretracheal or prelaryngeal lymph nodes metastasis, being consistent with the other studies reported (19,20).…”
Section: Discussionmentioning
confidence: 55%
“…Nevertheless, PTC confined to isthmus has been reported to be more aggressive than the nodule located at lobes ( 15 17 ). Young Chan Lee et al.…”
Section: Discussionmentioning
confidence: 99%
“…In such instances, molecular analysis of FNAC samples has recently gained in popularity as an adjunct to microscopic cytological evaluation. Many molecular markers, such as BRAF and RAS mutations and gene product aberrations, are promising as diagnostic and prognostic markers [15-17]. In general, molecular testing offers high specificity and positive predictive value, but sensitivity is low [18].…”
Section: Introductionmentioning
confidence: 99%